2010
DOI: 10.1111/j.1399-3038.2010.01035.x
|View full text |Cite
|
Sign up to set email alerts
|

International study of wheezing in infants: risk factors in affluent and non-affluent countries during the first year of life

Abstract: Risk factors for wheezing during the first year of life (a major cause of respiratory morbidity worldwide) are poorly known in non-affluent countries. We studied and compared risk factors in infants living in affluent and non-affluent areas of the world. A population-based study was carried out in random samples of infants from centres in Latin America (LA) and Europe (EU). Parents answered validated questionnaires referring to the first year of their infant's life during routine health visits. Wheezing was st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
103
2
35

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(158 citation statements)
references
References 29 publications
18
103
2
35
Order By: Relevance
“…Será que vale para nossa realidade? Foi demonstrado que as meninas são amamentadas por mais tempo que os meninos e que isto influenciaria no aparecimento de sibilância precoce, pois estes seriam apresentados mais cedo aos alimentos artificiais, contribuindo para a sensibilização precoce 9 . Entre os meninos o calibre das vias aéreas é menor quando comparado ao das meninas durante a infância, enquanto que durante a puberdade esta relação se inverte e isto favoreceria o aparecimento de sibilância nas adolescentes 27 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Será que vale para nossa realidade? Foi demonstrado que as meninas são amamentadas por mais tempo que os meninos e que isto influenciaria no aparecimento de sibilância precoce, pois estes seriam apresentados mais cedo aos alimentos artificiais, contribuindo para a sensibilização precoce 9 . Entre os meninos o calibre das vias aéreas é menor quando comparado ao das meninas durante a infância, enquanto que durante a puberdade esta relação se inverte e isto favoreceria o aparecimento de sibilância nas adolescentes 27 .…”
Section: Discussionunclassified
“…Estudos demonstraram diversos fatores de risco para sibilância precoce em crianças e sua relação com o posterior desenvolvimento de asma, como: prematuridade 7 ; tabagismo materno na gestação ou passivo após o nascimento 8,9 ; sexo masculino 9,10 ; infecções respiratórias 9,11 , notadamente pelo vírus respiratório sincicial 12 ; história familiar de asma ou antecedente pessoal de dermatite atópica ou de rinite 9,13 . Também foi demonstrada relação entre sibilância precoce e sensibilização precoce a alimentos ou aeroalér-genos, função pulmonar reduzida e nível sanguí-neo elevado de eosinófilos, com posterior persistência destes sintomas 3,14 .…”
Section: Introductionunclassified
“…The international results demonstrated a wide variation in the prevalences of occasional wheezing (< 3 episodes) and recurrent wheezing (≥ 3 episodes); in Brazil, among the seven cities in which analyses were made, the presence of at least 1 episode of wheezing ranged from 45.1% in Curitiba to 63.3% in Porto Alegre, whereas recurrent wheezing ranged from 18.2% in Recife to 27.0% in Porto Alegre. (2) Episodes of wheezing are related to viral respiratory infections, such as infection with respiratory syncytial virus (RSV), which induces wheezing in infants. Of the infants so affected, half will develop recurrent wheezing and one fourth will present with asthma after reaching school age.…”
Section: The Estudio Internacional De Sibilancias En Lactantes (Eislmentioning
confidence: 99%
“…In another study, infants in the city of Curitiba were found to have received overtreatment with asthma medications, which might be due to the availability of such medications in the public health care system or to the fact that the guidelines for the management of asthma are unknown or are not adhered to. (6) The comparison between the findings from the investigation of infants in Curitiba and those from the investigation of infants in the city of São Paulo, Brazil, (2) revealed that, in the latter, a high number of children with wheezing (recurrent or otherwise) received systemic corticosteroids ( Table 1). The information provided by the parents showed that, among the infants with recurrent wheezing in the city of São Paulo, when compared with those in the city of Curitiba, there was greater occurrence of nocturnal symptoms, of severe symptoms, of emergency room visits (71.5% vs. 22.9%), and…”
mentioning
confidence: 99%
“…1 Wheeze during first year of life is a very frequent condition worldwide: 45% experience at least one episode and 23% experience recurrent wheeze. 2,3 Recurrent cough and wheeze in infancy are common problems in general paediatric outpatient clinics and practice. 4,5 Atopic conditions such as asthma, atopic eczema, allergic rhinitis are prevalent significantly among Bangladeshi children.…”
Section: Introductionmentioning
confidence: 99%